Genetic Variability in the Indonesian Giant Clam (Tridacna crocea and Tridacna maxima) Populations: Implication for Mariculture and Restocking Program - Agus Nuryanto; Dedy Duryadi (Fakultas Biologi | Universitas Jenderal Soedirman, 2007)
Tridacna crocea and T. maxima are relatively abundant in the Indonesian coral reef. These two species are, however, under high presure due to exploitation for food, industry, and aquarium trade. It is, therefore, necessary to understand their biology, such as genetic variability within and between populations, before utilizing them for strain improvement and restocking, prior to the extinction of the populations of T. crocea and T. maxima. Here we amplified a length of 456 bp of the mitochondrial DNA cytochrome c oxidase I gene from Tridacna crocea and of 484 bp from T. maxima to asses the genetic variability within and between populations of both species. The results showed that both species have high genetic diversity and polymorphism within each local population. This provides a sufficient basis for selection of improved strain of T. crocea and T. maxima for mariculture. However, if the genetic variation led to genetic differentiation among populations due to the result of evolutionary adaptation, mixing genetically different populations may result in the break up of co-adaptation gene complexes. This might result in the loss of the physiological capacities of the parental populations.